The second immunoglobulin-like domain of the VEGF tyrosine kinase receptor Flt-1 determines ligand binding and may initiate a signal transduction cascade. - Davis-Smyth, T (1996)
Vascular endothelial growth factor (VEGF) is an angiogenic inducer that mediates its effects through two high affinity receptor tyrosine kinases, Flt-1 and KDR. Flt-1 is required for endothelial cell morphogenesis whereas KDR is involved primarily in mitogenesis. Flt-1 has an alternative ligand, placenta growth factor (PlGF). Both Flt-1 and KDR have seven immunoglobulin (Ig)-like domains in the extracellular domain. The significance and function of these domains for ligand binding and receptor activation are unknown. Here we show that deletion of the second domain of Flt-1 completely abolishes the binding of VEGF. Introduction of the second domain of KDR into an Flt-1 mutant lacking the homologous domain restored VEGF binding. However, the ligand specificity was characteristic of the KDR receptor. We then created chimeric receptors where the first three or just the second Ig-like domains of Flt-1 replaced the corresponding domains in Flt-4, a receptor that does not bind VEGF, and analyzed their ability to bind VEGF. Both swaps conferred upon Flt-4 the ability to bind VEGF with an affinity nearly identical to that of wild-type Flt-1. Furthermore, transfected cells expressing these chimeric Flt-4 receptors exhibited increased DNA synthesis in response to VEGF or PlGF. These results demonstrate that a single Ig-like domain is the major determinant for VEGF-PlGF interaction and that binding to this domain may initiate a signal transduction cascade.